Pengembangan Buku Ajar Pengantar Dasar Matematika Berbasis Kitab Taqrib Dalam Meningkatkan Kemampuan Literasi Mahasiswa - Mohammad Kholil; Mohammad Mukhlis (Jurnal Tadris Matematika, 2023)
The purpose of this study is to develop a textbook for introductory mathematics based on the taqrib book to improve student literacy skills and find out the feasibility, practicality, and effectiveness of textbook for introductory mathematics based on the taqrib that has been developed. The type of research used is Research and Development (R&D) which is designed using the Borg and Gall development model. The subjects of the development product trial in this study were students of the class 2022 semester 1 of the MTK1, MTK2, and MTK3 classes of mathematics education study program at FTIK UIN KHAS Jember. This research produces a textbook of introduction to basic mathematics based on the taqrib book as students' reference book in lectures on basic introduction to mathematics in semester 1. The resulting textbook is validated by three validators with validation results without any revisions, so the textbooks developed are feasible for use. Furthermore, the resulting textbooks were tested on 1st-semester students of the mathematics education study program at FTIK UIN KHAS Jember. The results of this product trial were 84.49% with a practical category. The mathematical literacy ability of students in semester 1 of the Mathematics Education study program has increased from a total average score of 77.32 to 86.27. Based on these results, it can be said that the use of textbooks for introductory mathematics based on taqrib books is very effective in improving students' mathematical literacy skills.